Participative and transversal projects as a learning base for acquiring a critical and socially responsible view of communication - Torres Valdés, Rosa María; Núñez Gómez, Patricia; Hanninen, Liisa Irene (Historia y Comunicación Social, 2014)
The project applies the methodology of Action Research in order to carry out a real communication campaign and simultaneously, analyze the motivations and perceptions of the partaking students. The reason why is to explore new formulas for involving students in the process of generating knowledge and teaching them a socially responsible and critical point of view of communication, as well as to offer them an opportunity to complete their CV with a work experience in collaboration with specialized staff from the agency and client, health and nutrition experts as well as university lecturers.